2014
DOI: 10.1093/bja/aeu093
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of the effect of intraoperative α2-adrenergic agonists on postoperative behaviour in children

Abstract: Undergoing general anaesthesia is distressing for children, with up to two-thirds demonstrating abnormal behaviours after their procedure, such as emergence delirium (ED) and post-hospitalization behaviour change. The aim of this systematic review was to determine the effect of intraoperative i.v. α₂-adrenergic agonists on postoperative behaviour in children. We included published full-text reports of randomized controlled trials involving children who received i.v. clonidine or dexmedetomidine after induction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
49
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 45 publications
7
49
0
1
Order By: Relevance
“…There has recently been increased interest in the use of a 2 -adrenergic receptor agonists. A systematic review and meta-analysis by Pickard et al [32], that included 12 randomised trials, concluded that both dexmedetomidine and clonidine reduced the incidence of emergence delirium, although recovery times were prolonged. One study [33] demonstrated that pre-operative infusion of dexmedetomidine reduced the incidence following eye surgery, although as this may be an impractical way to administer the drug whilst the patient is awake, intranasal administration is probably an acceptable alternative [34].…”
mentioning
confidence: 99%
“…There has recently been increased interest in the use of a 2 -adrenergic receptor agonists. A systematic review and meta-analysis by Pickard et al [32], that included 12 randomised trials, concluded that both dexmedetomidine and clonidine reduced the incidence of emergence delirium, although recovery times were prolonged. One study [33] demonstrated that pre-operative infusion of dexmedetomidine reduced the incidence following eye surgery, although as this may be an impractical way to administer the drug whilst the patient is awake, intranasal administration is probably an acceptable alternative [34].…”
mentioning
confidence: 99%
“…Several studies describe the beneficial effects of clonidine for premedication in pediatric anesthesia, prevention of emergence agitation, prolongation of postoperative analgesia as a supplement to regional anesthesia, reduction of the incidence of post-operative vomiting, and treatment of emergence delirium [6,[9][10][11][12][13]. Clonidine can also be used in opiate withdrawal treatment, attention deficit/hyperactivity disorder, Tourette's syndrome, schizophrenia and Korsakoff syndrome [1].…”
Section: Resultsmentioning
confidence: 99%
“…It has a sedative effect mediated by binding to post-synaptic alpha-2 receptors in the pontine locus ceruleus, reducing noradrenergic output and thereby facilitating the firing of inhibitory neurones, mainly, the gamma-aminobutyric acid system. Clonidine has an analgesic action through binding to alpha-2 receptors in the dorsal horn and supra-spinal sites and thereby reduce the release of P substance [1,5,6]. It also causes peripheral vasodilatation and a decrease in systolic blood pressure, heart rate and cardiac output by decreasing sympathetic nervous system activity.…”
mentioning
confidence: 99%
“…Emergence agitation in children was first described in the early 1960s and is characterized by a dissociated state of consciousness in which the child becomes inconsolable, irritable, uncooperative, and sometimes aggressive. Although temporary, it is an extremely distressing event for children, parents, and health professionals [10]. Prevalence of agitation varies from 25% to 80% in the literature, depending on the definition and criteria used by the authors [11].…”
Section: Comparative Study and Safe Dose Analysis Of Dexmedetomidine mentioning
confidence: 99%